The Pathogenesis of Tuberculosis: The Early Infiltrate of Post-primary (Adult Pulmonary) Tuberculosis: A Distinct Disease Entity - Hunter, Robert L. (Frontiers in Immunology, 2018)
It has long been recognize that tuberculosis (TB) induces both protective and tissue damaging immune responses. This paper reviews nearly two centuries of evidence that protection and tissue damage are mediated by separate disease entities in humans. Primary TB mediates protective immunity to disseminated infection while post-primary TB causes tissue damage that results in formation of cavities. Both are necessary for continued survival of Mycobacterium tuberculosis (MTB). Primary TB has been extensively studied in humans and animals. Post-primary TB, in contrast, is seldom recognized or studied. It begins as an asymptomatic early infiltrate that may resolve or progress by bronchogenic spread to caseous pneumonia that either fragments to produce cavities or is retained to produce post-primary granulomas and fibrocaseous disease. Primary and post-primary TB differ in typical age of onset, histopathology, organ distribution, x-ray appearance, genetic predisposition, immune status of the host, clinical course and susceptibility to protection by BCG. MTB is a highly successful human parasite because it produces both primary and post-primary TB as distinct disease entities in humans. No animal reproduces this sequence of lesions. Recognition of these facts immediately suggests plausible solutions, animal models and testable hypotheses to otherwise inaccessible questions of the immunity and pathogenesis of TB.